2020
DOI: 10.1007/s42438-020-00193-6
|View full text |Cite
|
Sign up to set email alerts
|

Quarantined, Sequestered, Closed: Theorising Academic Bodies Under Covid-19 Lockdown

Abstract: The term ‘quarantine’ is derived from the Italian quarantena, from quaranta, referring to the forty days of isolation traditionally imposed during the era of the Black Death in Europe. This paper examines this and related contemporary terms, in order to consider the complex and contradictory nature of enforced sites of isolation, with reference to the historical literature. The centrality of spatial practices in the current pandemic is emphasised, with a focus on the normally unobserved, micro practices of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…In the recent Moving to Online Teaching and Homeworking interview study with academics under lockdown, Gourlay (2020b) found a range of orientations to the conditions of enforced confinement among the participants. The analysis revealed a situation which in some ways corresponded to traditional notions of being under 'quarantine' in order to shelter from a dangerous disease and protect others.…”
Section: Academic Geographies Under Covid-19mentioning
confidence: 99%
“…In the recent Moving to Online Teaching and Homeworking interview study with academics under lockdown, Gourlay (2020b) found a range of orientations to the conditions of enforced confinement among the participants. The analysis revealed a situation which in some ways corresponded to traditional notions of being under 'quarantine' in order to shelter from a dangerous disease and protect others.…”
Section: Academic Geographies Under Covid-19mentioning
confidence: 99%
“…The University College London Institute of Education 'Moving to Teaching Online and Homeworking' research project was funded and established at the start of the 2020 March lockdown, in order to investigate the impact the move to working online at home was having on academic and professional services staff across UCL (Gourlay 2020;Littlejohn 2020). Institutional ethical approval was secured, which included commitments to informed consent, confidentiality and anonymity; all names used in this paper are pseudonyms.…”
Section: The Studymentioning
confidence: 99%
“…These blurred or abandoned boundaries took many forms; some were temporal, with interviewees reporting working longer hours, or work spilling into the weekend, due to the lack of punctuation normally provided by commuting to and from the campus. Another prominent blurred boundary was spatial, with most of the participants having converted an area of their home into a work space, again obscuring the distinction between home and work, with domestic spaces such as kitchen tables, a nursery chair, and a bedside table converted to work areas (Gourlay 2020). For some participants, boundaries were felt to have been eroded in terms of identities, with the role of parent and caregiver being intermingled with the professional role (Gourlay 2020).…”
Section: Interview Findings: Semiotic Assemblages and Boundary Workmentioning
confidence: 99%
“…Working parents were expected to ensure that their children continued to follow the routine of the school day during the lockdown period. This had to be combined with working remotely, which continued to carry expectations of 'professionalism' and conformity to the ideal, domestically unburdened worker (see Gourlay, 2020). The increased pressure of juggling caregiving and other social reproduction with professional obligations was described by one commentator as a 'never-ending shift' (Boncori, 2020).…”
Section: A Crisis Of Depletion and A Lack Of Resiliencementioning
confidence: 99%